Fluoride Content in Foods and Beverages From Mexico City Markets and Supermarkets. Issue 4 (December 2019) - Cantoral, Alejandra; Luna-Villa, Lynda Cristina; Mantilla-Rodriguez, Andres A.; Mercado, Adriana; Lippert, Frank; Liu, Yun; Peterson, Karen E.; Hu, Howard; Téllez-Rojo, Martha M.; Martinez-Mier, Esperanza A.
Background: Sources of fluoride exposure for Mexicans include foods, beverages, fluoridated salt, and naturally fluoridated water. There are no available data describing fluoride content of foods and beverages consumed in Mexico. Objective: To measure the content of fluoride in foods and beverages typically consumed and to compare their content to that of those from the United States and the United Kingdom. Methods: Foods and beverages reported as part of the Mexican Health and Nutrition Survey (n = 182) were purchased in the largest supermarket chains and local markets in Mexico City. Samples were analyzed for fluoride, at least in duplicate, using a modification of the hexamethyldisiloxane microdiffusion method. Value contents were compared to those from the US Department of Agriculture and UK fluoride content tables. Results: The food groups with the lowest and highest fluoride content were eggs (2.32 µg/100 g) and seafood (371 µg/100 g), respectively. When estimating the amount of fluoride per portion size, the lowest content corresponded to eggs and the highest to fast foods. Meats and sausages, cereals, fast food, sweets and cakes, fruits, dairy products, legumes, and seafood from Mexico presented higher fluoride contents than similar foods from the United States or the United Kingdom. Drinks and eggs from the United States exhibited the highest contents, while this was the case for pasta, soups, and vegetables from the United Kingdom. Conclusion: The majority of items analyzed contained higher fluoride contents than their US and UK counterparts. Data generated provide the first and largest table on fluoride content, which will be useful for future comparisons and estimations.